2008
DOI: 10.1016/j.immuni.2008.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Enhances Foxp3 Induction Indirectly by Relieving Inhibition from CD4+CD44hi Cells

Abstract: Summary The CD4+Foxp3+ lineage of regulatory T (Treg) cells plays a key role in controlling immune and autoimmune responses. Treg cells originate primarily during T cell differentiation in the thymus, but conversion of mature T lymphocytes to Foxp3-positivity can be elicited by several means, including activation in the presence of transforming growth factor (TGF)β in vitro. Retinoic Acid (RA), the ubiquitous morphogen that exerts a particular shepherding effect on the gut immune system, increases TGFβ–induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
284
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(302 citation statements)
references
References 55 publications
15
284
2
1
Order By: Relevance
“…Several studies have demonstrated that RA can negatively affect the differentiation of T H 17 cells [26][27][28][29] although the precise mechanisms remain unclear. Based on our data showing heightened IL-17A production by HIC1-deficeint T H 17 cells in vitro and in vivo, we hypothesized that expression of HIC1 would be required for the RA-dependent reduction in T H 17-cell differentiation.…”
Section: Hic1 Is Not Required For Inhibitory Effects Of Ra On T H 17-mentioning
confidence: 99%
“…Several studies have demonstrated that RA can negatively affect the differentiation of T H 17 cells [26][27][28][29] although the precise mechanisms remain unclear. Based on our data showing heightened IL-17A production by HIC1-deficeint T H 17 cells in vitro and in vivo, we hypothesized that expression of HIC1 would be required for the RA-dependent reduction in T H 17-cell differentiation.…”
Section: Hic1 Is Not Required For Inhibitory Effects Of Ra On T H 17-mentioning
confidence: 99%
“…40,41 It remains unclear whether RAPA selectively suppresses the expansion of non-Treg cells, thereby indirectly promoting the expansion of Foxp3 1 Treg cells. 16 Although a comparison study has shown that both RAPA and atRA had similar effects on promoting and stabilizing Treg cells during their expansion, 42 a more recent study demonstrated that atRA exhibits superior efficacy relative to RAPA for stabilizing nTreg cells under inflammatory conditions. 23 The mechanism by which atRA stabilizes nTreg cells is discussed below.…”
Section: Foxp3 and Treg Cell Subsetsmentioning
confidence: 99%
“…Recent studies revealed that atRA regulates the differentiation of Th cells and Foxp3 1 Treg cells. 16,17 Additionally, atRA promotes the development and function of CD4 1 iTreg cells, although its effect on CD8 1 iTreg cells is minimal. [18][19][20][21] Moreover, atRA also helps preserve nTreg cell stability under inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of TGF-β, together with retinoic acid (RA), may be required for induction of Foxp3 + Tregs to suppress potentially detrimental inflammatory Th17 cell responses [57][58][59][60][61][62]. The inhibition of IL-6 receptor (IL-6Rα) expression by RA, suggested by a recent study, provides at least in part an explanation for how RA antagonizes Th17 cell differentiation [63]. Foxp3 inhibits RORγt-directed IL-17 expression in mouse T cells, but it remains to be determined whether this also occurs in humans.…”
Section: In Vivo Relevance and Implicationsmentioning
confidence: 99%